The Role of Online Promotion and Its Effect on Destination Loyalty - Melania, Karmelia; Ellyawati, Jeanne (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2018)
This study aims to analyze the influence of online promotion on destination loyalty directly or indirectly through destination awareness and tourist satisfaction. This study also examined the influence of destination awareness on tourist satisfaction. A sample of 250 domestic tourists was recruited as respondents using purposive sampling method. Data were collected with survey design and analyzed using hierarchical regression model. The results show both destination awareness and tourist satisfaction are important variables that should be considered by marketers to capture the opportunity of tourists visit. It is found that information from online promotion will trigger awareness and increase tourist satisfactionKeywords: online promotion, destination awareness, tourist satisfaction, destination loyalty